FluOil: A Novel Tool for Modeling the Transport of Oil-Particle Aggregates in Inland Waterways - Li, Yilan; Zhu, Zhenduo; Soong, David T.; Khorasani, Hamed; Wang, Shu; Fitzpatrick, Faith; Garcia, Marcelo H. (Frontiers in Water, 2022)
.